Penerapan Sistem Akuntansi Sumber Daya Manusia Terhadap Kinerja Karyawan Pada Bengkel Daniyah Lubis Motor - Mutiara Oktaviani Putri; Ulviana Agustina; Hasna Lutfi Indriani; Ersha Wiriani Safitri; Siti Rodiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The company's problems still revolve around human resources surviving in the era of globalization. This research aims to analyze accounting systems, human resources on employee performance. One of the key elements for the successful implementation of an efficient organization is human resources. Facilities, abundant infrastructure and resources all support this, but without the help of human resources, company operations cannot be handled effectively. A reliable, high-performance power source is required. The increasing complexity of the legal system, the awareness that humans are a very useful instrument for increasing productivity and understanding the negative impacts of ineffective human resource management are the main causes of the increasing importance of human resources. The analytical method that the author uses in this research is comparative and qualitative descriptive methodology. The results of the research show that: the implementation of the human resources employee accounting system for the performance of the Daniyah Lubis Motor Workshop is in accordance with the study theory. In implementing the Human Resources Accounting system, Daniyah Lubis Motor Workshop is still less effective, this can be seen from the contribution of employee performance.